PKM Pembuatan Media Pembelajaran IPA dan Matematika Berbasis Bahan Lokal - Sukarjita, I Wayan; Yusuf, Yusniati H. M.; Warasabon, Dominikus; Maubuthy, Markus Simeon K. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Nusa Cendana, 2024)
Community service activities have been carried out in the form of activities to create science and mathematics learning media based on local materials for elementary school teachers at GMIT Manumuti Kupang. This activity lasted for two days at the GMIT Manumuti Elementary School Hall, Kupang Regency. The aim of this activity is to provide insight into knowledge and skills regarding making science and mathematics media using local materials. This service activity uses lecture, discussion, question and answer, simulation, practice and training methods. The results of the activity conclude (1) that this service activity has improved the skills of GMIT Manumuti Tarus Elementary School partner teachers in designing and making science and mathematics learning media based on local materials to make it easier for students to understand basic science and mathematics concepts, (2) This service activity has provided the basics of Science and Mathematics to partner teachers at GMIT Manumuti Tarus Elementary School as a concept for teaching science and mathematics material to students so that learning becomes more meaningful.